study on promotional practices adopted by women of Self Help Group (SHG) in Pune District and role of microfinance - Dr Madhura Pimplapure , Dr Rajlaxmi Pramod Pujar (International Journal of Advanced Science and Technology, 2020)
In recent time, before the analysis of the empowerment of women through Self Help Groups, which have been formed with a logic and reason in view of the need, it will be more fruitful to look through the evolution and progress of self help movement that has occurred in the developing country like India, so that a complete understanding can be acquired and more so how far empowerment of women has been gained with regard to the objectives of the SHGs, to just understand, how far the formation of SHGs and the fulfilment of their core objectives have been successful, and whether the rural people, especially the deprived women have received socio-economic empowerment through SHGs may be vividly and illustratively examined. The formal institutions have been ineffective in offering financial services to the deprived sections of society. Having completely discouraged by their performance, the Government of India initiated to promote another apex bank to take care of the financial needs of the poor, informal sector and rural areas. Besides, the decline of cooperative in the sixties and seventies is widely attributed to the government’s direct promotional role, their artificial propping up through subsidies and undue interference in management. Consequently, NABARD desired to develop a new channel to reach the poor, particularly women, free from government subsidies and interference. In spite of the decline of the cooperatives, the search for an appropriate community based structure perfectly matched to the rural poor women continued and women’s groups known as Self-Help Groups (SHGs) emerged in the late eighties and the early nineties around rotating mutual savings and credit as a stable and viable alternative. It was a development innovation in its own right. The purpose of this primary research is to investigate promotional practices currently adopted by SHGs in Pune District. The study also attempts to understand the awareness and penetration of newer promotional tools. Hypothesis testing is done by ANOVA test to understand relation between business success and adoption of appropriate sales and promotional practices and impact of success of few SHGs in growth of more self-help groups. Since microfinance has played a major role in meeting the financial requirements of self-help groups, the role of microfinance has also been stated in this research study.